Localization and Functional Parameter Reconstruction of Suspicious Breast Lesions by Near Infrared/Ultrasound Dual Modal Imaging - Xu, R.X.; Bo Qiang; Olsen, J.O.; Povoski, S.P.; Yee, L.D.; Mao, J. (Conference proceedings (IEEE Engineering in Medicine and Biology Society. Conf.), 2005)
A novel imaging scheme integrating a continuous wave (CW) hand held near infrared tissue imager and a portable ultrasound probe was proposed for evaluation of suspicious breast lesions. A new methodology was developed to reconstruct functional properties of the lesion and the surrounding tissue based on the optical measurement of the diffusive light and the ultrasound measurement of the tumor morphology. The first order Born approximation was used to solve the absorption coefficients for both the tumor tissue and the background tissue assuming that optical properties within each tissue type are uniform. A compression force was applied by the handheld near infrared imager to the breast tissue in order to enhance the optical contrast. The force was monitored by a built-in load cell. 2D projection algorithm was used to find the center of the tumor and to co-register the near infrared image with the ultrasound image. The proposed imaging scheme was tested by a clinical trial where both near infrared and ultrasound data were collected on subjects' breast tissues with embedded suspicious lesions. 3D image algorithm on single patient successfully reconstructed the oxygen saturation and the hemoglobin concentration in both the tumor area and the surrounding tissue. More data collection and analysis are required to confirm this imaging scheme